Persepsi Karyawan Terhadap Penerapan Audit Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) di PT Hitachi Astemo Bekasi Powertrain Systems - Adi Wirawan; Yuni Pratikno; Widya Nengsih (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This study examines employee perceptions of the implementation of Occupational Safety and Health Management System (SMK3) audits, considering that audit effectiveness is closely related to employees’ understanding and acceptance of the process. Although SMK3 audits are regularly conducted, several audit findings indicate that improvements are still required in certain aspects of implementation. This research aims to analyze employee perceptions of SMK3 audit implementation, identify factors influencing these perceptions, and assess the impact of SMK3 audits on employee work behavior and safety compliance. The study employed a descriptive qualitative approach with a case study design at PT Hitachi Astemo Bekasi Powertrain Systems. Data were collected through direct observation, in-depth interviews with employees involved in the SMK3 audit process, and documentation review. Data analysis was carried out using descriptive qualitative techniques to interpret employees’ experiences, views, and responses toward the audit process. The results show that employee perceptions of SMK3 audit implementation tend to be neutral to positive. Positive perceptions are influenced by employees’ understanding of audit objectives, management support, effective communication from auditors, and the presence of a strong safety culture. However, audit results identified that 15 out of 166 SMK3 criteria still required improvement, particularly in regulatory compliance, risk evaluation, training effectiveness, emergency preparedness, and workplace safety controls. Overall, SMK3 audit implementation contributes positively to improving safe work behavior, compliance with safety procedures, and employee productivity.